A pathway for every product? Tools to discover and design plant metabolism. (August 2018) - Jeffryes, James G.; Seaver, Samuel M.D.; Faria, José P.; Henry, Christopher S.
Highlights: A wealth of computational tools have been developed to explore metabolic pathways. Constraint-based and graph-based pathway tools are described. Successes and limitations of retrosynthesis tools are reviewed. Applications of novel reaction predictions to evaluate side reactions are explored. Abstract: The vast diversity of plant natural products is a powerful indication of the biosynthetic capacity of plant metabolism. Synthetic biology seeks to capitalize on this ability by understanding and reconfiguring the biosynthetic pathways that generate this diversity to produce novel products with improved efficiency. Here we review the algorithms and databases that presently support the design and manipulation of metabolic pathways in plants, starting from metabolic models of native biosynthetic pathways, progressing to novel combinations of known reactions, and finally proposing new reactions that may be carried out by existing enzymes. We show how these tools are useful for proposing new pathways as well as identifying side reactions that may affect engineering goals.